2017
DOI: 10.1089/bfm.2016.0142
|View full text |Cite
|
Sign up to set email alerts
|

Early Breast Milk Pumping Intentions Among Postpartum Women

Abstract: Introduction: Milk expression has become common, but little is known about women's intentions and motivations for pumping. Our objectives were to measure, among newly postpartum women, intentions related to breast milk feeding and pumping, reasons for intending to pump, and timing of pumping initiation. Methods: We conducted a cross-sectional study at a large university hospital in 2015 using a convenience sample of 100 women before their discharge following delivery, who intended to feed their infant breast m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…This aligns with our finding that breastfeeding self-efficacy scores were significantly lower among Study B participants using expressed HM at 2 weeks postpartum. Other studies have found difficulties feeding at the breast and concerns about milk supply to be commonly reported reasons for expressed HM use during the hospital stay6 34 and up to 4.5 months postpartum 3 4 32. These are also the most common reasons reported for early cessation of any and exclusive HM feeding 35 36.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with our finding that breastfeeding self-efficacy scores were significantly lower among Study B participants using expressed HM at 2 weeks postpartum. Other studies have found difficulties feeding at the breast and concerns about milk supply to be commonly reported reasons for expressed HM use during the hospital stay6 34 and up to 4.5 months postpartum 3 4 32. These are also the most common reasons reported for early cessation of any and exclusive HM feeding 35 36.…”
Section: Discussionmentioning
confidence: 99%
“…In the research ((Loewenberg Weisband et al, 2017) declared two third of women pump temporary for increasing their breastfeeding supply. The result of interview has been conducted.…”
Section: B Breastfeeding Productionmentioning
confidence: 99%
“…In line with the result (Flaherman et al, 2016) mentioned the painful experience when conducting breast pump. Based on (Loewenberg Weisband et al, 2017) examined that the risk of breast which often identified is breast tissue damage, infection, and contamination of breastmilk. LC (Lactation Consultant's) stated this problem frequently is caused by the usage or the choice of pump.…”
Section: Outcome Negative Of Breast Pumpmentioning
confidence: 99%
“…In higher income countries, the mode of breastfeeding has been changing, and there is an increasing trend of expressed human milk feeding (Fan et al, in press). A high proportion of new mothers express their milk within the postpartum hospital stay, with rates ranging from 15% in the United States (Loewenberg Weisband et al, 2017), to 46% in Australia (Johns et al, 2013), and 87% in China (Jiang et al, 2015). Undoubtedly, feeding expressed human milk to infants provides greater health benefits than feeding human milk substitutes.…”
mentioning
confidence: 99%
“…Among people with healthy full-term infants, breastfeeding- and work-related factors, including experiencing breastfeeding problems (Felice et al, 2016), early infant formula supplementation (Bai et al, 2017), and returning to work, are associated with expressed human milk feeding (Felice et al, 2016). Among the participants’ self-reported reasons, breast engorgement (Demirci & Bogen, 2017; Johns et al, 2016), allowing or needing others to feed the baby (Johns et al, 2016), and breastfeeding problems (Loewenberg Weisband et al, 2017) were the most common reasons for expressed human milk feeding.…”
mentioning
confidence: 99%